2008
DOI: 10.1007/s11426-008-0099-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical, quantum chemical and SEM investigation of the inhibiting effect and mechanism of ciprofloxacin, norfloxacin and ofloxacin on the corrosion for mild steel in hydrochloric acid

Abstract: The inhibiting effect and mechanism of 1-cyclopropyl-6-fluoro-1,4-dihydro -4-oxo-7-(1-piperazinyl) -3-quinoline carboxylicacid(ciprofloxacin), 1-ethyl-6-fluoro-1,4-dihydro-4-oxo-7-(1-piperazinyl)-3-quinoline carboxylic acid (norfloxacin) and (−)-(S)-9-fluoro-2,3-dihydro-3-methyl-10-(4-methyl-1-piperazinyl)-7-oxo-7 H-pyrido(1,2,3-de)-1,4-benzoxazine-6 carboxylic acid (ofloxacin) on the corrosion of mild steel in 1 mol/L HCl have been studied using electrochemical method, quantum chemical method and SEM at 303 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In turn, the inhibitors molecules could protonate in the acidic solution, the protonated inhibitor and water molecules would be attracted on the metal surface by physical action, then there was a possibility that the inhibitors and Fe atoms could interact though the empty orbital and the occupied orbital each other, and in part 3.6, this work showed some results about the interaction between them on the microlevel [25].…”
Section: Thermodynamic Behavior Of Inhibitor Molecularmentioning
confidence: 73%
“…In turn, the inhibitors molecules could protonate in the acidic solution, the protonated inhibitor and water molecules would be attracted on the metal surface by physical action, then there was a possibility that the inhibitors and Fe atoms could interact though the empty orbital and the occupied orbital each other, and in part 3.6, this work showed some results about the interaction between them on the microlevel [25].…”
Section: Thermodynamic Behavior Of Inhibitor Molecularmentioning
confidence: 73%
“…It is widely applied in the analysis of corrosion inhibition performance and the interaction of corrosion inhibitors and interfaces [29]. The B3LYP functional was applied within the context of Gaussian 09 [30], using the 6-31+G(d,p) basis set. From quantum chemical study, the mechanism of corrosion, inhibitor adsorption on metal surfaces, and the merits of corrosion inhibitors can easily be studied.…”
Section: Methodsmentioning
confidence: 99%
“…In chemisorption, one of the reacting species acts as an electron donor and the other one act as an electron acceptor. The energy of the highest occupied molecular orbital (E HOMO ) measures the tendency towards the donation of electron by a molecule [30]. High values of E HOMO have a tendency of the molecule to donate electrons to appropriate acceptor molecules.…”
Section: Methodsmentioning
confidence: 99%
“…According to electrochemical impedance spectroscopy (EIS) data, Cefatrexyl can inhibit iron corrosion in HClO 4 , H 2 SO 4 and H 3 PO 4 [22]. A few antibiotics, namely, Ciprofloxacin (I), Norfloxacin (II), Ofloxacin (III) [23] and Gatifloxacin (IV) [24]: efficiently hinder carbon steel corrosion in cold HCl solutions. It has been shown that a temperature (t) rise decreases the inhibitory properties of Gatifloxacin [24].…”
Section: Introductionmentioning
confidence: 99%